Funding of a €77.000 Feasibility Study - Keivanidis, Panagiotis E. (My University, 2026)
Co-principle investigator in a six-months long feasibility study project of €77.000, offered by the industrial entity OMET s.r.l. (IT), for validating the capability of an OMET press machine to support the production of plastic solar cells with roll-to-roll process.
Keywords: Natural sciences